Issues and Current Trends of Hollow-Fiber Mixed-Matrix Membranes for CO2 Separation from N2 and CH4 - Mubashir, M. (Wiley-VCH Verlag, 2018)
To control CO2 emission from industries, membrane technology is preferred over conventional technologies due to its numerous advantages including reliability, operational simplicity, and low capital cost. Hollow-fiber mixed-matrix membranes (HFMMMs) exhibit great potential for CO2 separation. Various inorganic fillers were incorporated into different types of polymeric materials for fabrication of HFMMMs. This review focuses on the performance and issues of HFMMMS based on various materials for CO2/CH4 and CO2/N2 separation. Major features are reflected in the following three aspects: comprehensive study on the performance of HFMMMs for CO2/N2 and CO2/CH4 separation, issues with the fabrication of HFMMMs in CO2/N2 and CO2/CH4 separation, and prediction of transport models for HFMMMs in gas separation. Â© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim